2014
DOI: 10.1371/journal.pone.0091995
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Negativity of Sad Syllables Is Absent in Patients with Major Depressive Disorder

Abstract: BackgroundMajor depressive disorder (MDD) is an important and highly prevalent mental disorder characterized by anhedonia and a lack of interest in everyday activities. Additionally, patients with MDD appear to have deficits in various cognitive abilities. Although a number of studies investigating the central auditory processing of low-level sound features in patients with MDD have demonstrated that this population exhibits impairments in automatic processing, the influence of emotional voice processing has y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
(59 reference statements)
4
13
0
Order By: Relevance
“…Pang et al (2014) found that sad prosodies in meaningless words did not elicit aMMN in comparison to neutral prosody in depression patients while no differences were found for happy or angry prosody in comparison to healthy controls. The aMMN did not correlate with depressive symptoms.…”
Section: Mood Disordersmentioning
confidence: 75%
See 2 more Smart Citations
“…Pang et al (2014) found that sad prosodies in meaningless words did not elicit aMMN in comparison to neutral prosody in depression patients while no differences were found for happy or angry prosody in comparison to healthy controls. The aMMN did not correlate with depressive symptoms.…”
Section: Mood Disordersmentioning
confidence: 75%
“…The lack of correlation between aMMN Pang et al, 2014;Takei et al, 2009) and depression symptoms suggests that sensorycognitive deficit in depression is a trait-not a state-dependent phenomenon.…”
Section: Mood Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the concurrent processing of vocal information was found to take place in early stages of information processing-that is, within the first 200 ms after voice stimulus onset (Beauchemin et al, 2006;Charest et al, 2009;Holeckova, Fischer, Giard, Delpuech, & Morlet, 2006;Kaganovich et al, 2006;Knösche, Lattner, Maess, Schauer, & Friederici, 2002;Titova & Näätänen, 2001). Besides the parallel processing of voice information, MMN studies demonstrated that concurrent linguistic processes (e.g., phonological, lexical, semantic, grammatical, and pragmatic) occur very early in the information-processing stream within the MMN time window (Kujala et al, 2010;Kujala, Tervaniemi, & Schröger, 2007;Näätänen et al, 2007;Pakarinen et al, 2009;E. Pang et al, 1998;Pulvermüller & Shtyrov, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, if these processes are not modulated by stimulus complexity, then the electrophysiological signatures of self-generated and nonself voice processing should be similar in the VCC and WCC conditions. Since we controlled for the physical differences between the voice stimuli (in line with earlier MMN studies: Graux et al, 2013;Graux et al, 2015;Leitman, Foxe, Sehatpour, Shpaner, & Javitt, 2009;Leitman, Sehatpour, Garidis, Gomez-Ramirez, & Javitt, 2011;X. Pang et al, 2014;Schirmer & Escoffier, 2010;Schirmer, Simpson, & Escoffier, 2007;Schirmer, Striano, & Friederici, 2005), using a Blike from like^subtraction approach, we hypothesized a nonsignificant association between voice acoustic properties and ERP measures of self-generated voice processing.…”
mentioning
confidence: 99%